Sewage sludge fertilizers in urban and forest park economy - Katsadze V. A.; Svoikin F. V.; Bubnov S. N.; Prokopyeva D. E.; Taraban M. V.; Studnikov P. E.; Kudryashov E. I. (BIO Web of Conferences)
This paper examines the use of fertilizers based on the sewage sludge in urban and forest park economy. The mentioned technologies allow achieving high agrochemical indicators and eliminating pathogenic microorganisms, which makes sewage sludge a valuable resource for increasing agricultural productivity and improving the condition of urban vegetation. The work is interesting for specialists in the field of agronomy, ecology and urban management.